Efficiency verification of a horizontal flow barrier via flowmeter tests and multilevel sampling. Issue 17 (24th May 2012) - Mastrocicco, M.; Sbarbati, C.; Colombani, N.; Petitta, M.
Abstract: The remediation strategy for an industrial site located in a coastal area involves a pump and treat system and a horizontal flow barrier (HFB) penetrating the main aquifer. To validate the groundwater flow conceptual model and to verify the efficiency of the remediation systems, we carried out piezometric measurements, slug tests, pumping tests, flowmeter tests and multilevel sampling. Flowmeter tests are used to infer vertical groundwater flow directions, and base exchange index is used to infer horizontal flow directions at a metric scale. The selected wells are located both upstream and downstream of the HFB. The installation of the HFB produced constraints to the groundwater flow. A stagnant zone of contaminated freshwater floating over the salt wedge in the upper portion of the aquifer is detected downstream of the HFB. This study confirms that the adopted remediation system is efficiently working in the area upstream of the HFB and even downstream in the bottom part of the aquifer. At the same time, it has also confirmed that hot spots are still present in stagnant zones located downstream of the HFB in the upper part of the aquifer, requiring a different approach to accomplish remediation targets. The integrated approach for flow quantification used in this study allows to discriminate the direction and the magnitude of groundwater fluxes near an HFB in a coastal aquifer. Copyright © 2012 John Wiley & Sons, Ltd.